Usando ZMET para explorar la conciencia de marca de ferias comerciales de emprendimiento creativo - Gamarra Olortegui, Alexa (2023)
Trade fairs have become a key factor in the promotion of creative and artistic industry ventures. Despite their importance, little is known about the attributes that shape the image of these events in the consumer's mind. Adopting the eight steps of Zaltman's Metaphor Elicitation Technique (ZMET), this study empirically examines the attributes and inner meanings of brand awareness through the metaphorical expression of its users. The results provide 11 thematic categories, including diversity, experience, styles, positive emotions, small universes, among others. The findings allow establishing new perspectives for marketing management for the creative industry in the future.